Przesłanki kredytowania kontrahentów w obrocie gospodarczym - Zawadzka, Danuta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
In the paper, the author concentrates on the companies' motives for trade credit in commercial transactions, in the context of the advantages and costs of it, with reference to the economy development in macroeconomic depiction. It is based on literature research. The author describes the huge range of the factors influencing companies' decisions. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 705-713